Impact of Media Law and Regulation on Radio Programing Diversity in Kenya - Wekesa , Allan; Mberia, Hellen; Omoke , Lilian (International Journal of Communication and Public Relation, 2023)
Purpose: All around the world, radio is regulated. The extent of the regulation and how it is done varies. Regulation takes many forms, ranging from clauses in national constitutions and laws to administrative procedures and technical specifications. This study examined how media laws and regulations affect radio programming diversity in Kenya. Methodology: The study adopted a mixed research design method, data was gathered through questionnaires and interviews and analyzed using descriptive and inferential statistics. Findings: The findings revealed that despite the importance of media laws and regulations to journalism practice, journalists' adherence to media laws and ethics was low. It was also established that journalists contravened media laws and ethics because of sycophancy, security reasons, desperation, greed, ethical dilemmas, ignorance of media laws and ethics, and laziness. Unique Contribution to Theory, Practice and Policy: The study was rooted on the normative theory of the press. According to Siebert, F., Peterson, T., & Schramm, W. (1956) A Normative theory describes an ideal way for a media system to be controlled and operated by the government, authority, leader and public. On its contribution to practice, the study calls on the Media Council of Kenya in conjunction with the Kenya Union of Journalists to enhance interaction between gatekeepers and reporters especially on ethical concerns in order to enhance adherence to the code of conduct.